Regulation of cytoskeletal dynamics by redox signaling and oxidative stress: implications for neuronal development and trafficking - Carlos eWilson (Frontiers in Cellular Neuroscience, 2015)
A proper balance between chemical reduction and oxidation (known as redox balance) is essential for normal cellular physiology. Deregulation in the production of oxidative species leads to DNA damage, lipid peroxidation and aberrant post-translational modification of proteins, which in most cases induces injury, cell death and disease. However, physiological concentrations of oxidative species are necessary to support important cell functions, such as chemotaxis, hormone synthesis, immune response, cytoskeletal remodeling, Ca2+ homeostasis and others. Recent evidence suggests that redox balance regulates actin and microtubule dynamics in both physiological and pathological contexts. Microtubules and actin microfilaments contain certain amino acid residues that are susceptible to oxidation, which reduces the ability of microtubules to polymerize and causes severing of actin microfilaments in neuronal and non-neuronal cells. In contrast, inhibited production of reactive oxygen species (e.g., due to NOXs) leads to aberrant actin polymerization, decreases neurite outgrowth and affects the normal development and polarization of neurons. In this review, we summarize emerging evidence suggesting that both general and specific enzymatic sources of redox species exert diverse effects on cytoskeletal dynamics. Considering the intimate relationship between cytoskeletal dynamics and trafficking, we also discuss the potential effects of redox balance on intracellular transport via regulation of the components of the microtubule and actin cytoskeleton as well as cytoskeleton-associated proteins, which may directly impact localization of proteins and vesicles across the soma, dendrites and axon of neurons.